Economic Consequences of the COVID-19 Outbreak: the Need for Epidemic Preparedness - Anton Pak; Oyelola A. Adegboye; Adeshina I. Adekunle; Kazi M. Rahman; Kazi M. Rahman; Emma S. McBryde; Damon P. Eisen (Frontiers Media S.A., 2020)
COVID-19 is not only a global pandemic and public health crisis; it has also severely affected the global economy and financial markets. Significant reductions in income, a rise in unemployment, and disruptions in the transportation, service, and manufacturing industries are among the consequences of the disease mitigation measures that have been implemented in many countries. It has become clear that most governments in the world underestimated the risks of rapid COVID-19 spread and were mostly reactive in their crisis response. As disease outbreaks are not likely to disappear in the near future, proactive international actions are required to not only save lives but also protect economic prosperity.